An analysis of MUHS MBBS community medicine theory examination papers I and II as per blue printing perspective - Chauhan, Rambadan Phoolchand (International Journal Of Community Medicine And Public Health, 2019)
Background: Blue print is a scientific tool to set an examination question paper. In this study, an attempt has been made to know whether the MUHS MBBS community medicine theory examination papers (I and II) are representative of the MUHS syllabus. Methods: MUHS community medicine examination papers were collected from various sources. The syllabus is declared by MUHS for both the papers. I conveniently divided each paper syllabus into 14 divisions as per chapters given in Park’s Textbook of Preventing and Social Medicineand MUHS suggestions. A working guideline of ‘question paper analysis’ was framed and validated by fellow faculties. The question papers were grouped into 4 categories based upon the number of deficiency scores: good (0 to -1), fair (-2 to -3), unsatisfactory (-4 to -5) and poor (-6 and below). Results: In paper I (sections ‘B+C’), total 33/35 papers were analyzed. ‘Good papers’ were 7 (21%), ‘fair papers’ were 14 (42%), ‘unsatisfactory papers’ were 8 (24%) and ‘poor papers’ were 4 (12%). In paper II (sections ‘B+C’), total 33/35 papers were analyzed. ‘Good papers’ were 2 (6%), ‘fair papers’ were 17 (52%), ‘unsatisfactory papers’ were 9 (27%) and ‘poor papers’ were 5 (15%). MCQ papers (22/70) analysis showed that 13(59%) MCQ papers were good, 7(32%) were fair and 2 (9%) were unsatisfactory. Conclusions: The paper-setting at MUHS community medicine paper I and paper II is not appropriate for syllabus representation.